ADSORPSI LIMBAH PB MENGGUNAKAN APLIKASI CARBON NANO TUBE TERINTEGRASI DENGAN SISTEM LAHAN BASAH BANTARAN SUNGAI GAJAH WONG - Melati, Asih; Sulistyawati, Eka; Nugraheni, Ika (IAIN Batusangkar, 2016)
As a heavy polluted river in Yogyakarta, Gajah Wong River has been the target of Environment Agency (BLH) for its protection and water treatment program. Our preliminary research shows it had DO 0 mg/L, BOD 27, 86 mg/L, COD 79, 49 mg/L, Pb 0,03 mg/L and PO4 3,250 mg/L. The aim of this research was exploring the effectiveness of water treatment system using carbon nano tube based on coconut shells activated carbon integrated with wetland system. The Carbon nano tube was synthesized by using CVD methods while wetland system contains plants (which absorb pollutants. The result of this research are participated from Gajah Wong community and the water become more purify signed by BOD, DO, PO4 and COD normal value.